The Nicaragua Judgment and the Use of Force – 30 Years Later (Polish Yearbook of International Law, 2016)
In light of contemporary circumstances, on the 30th anniversary of the Nicaragua judgment it is worth revisiting and considering again certain legal problems decided by – and raised by – the ICJ judgment. This article addresses the importance of the judgment in terms of international legal regulations on the use of force. First and foremost, the article examines the concept of armed attack based on the “gravity” criterion elaborated by the Court and the exercise of the right of self-defence. Moreover, the relationship between customary international law and treaty law, as well as forcible counter-measures and military actions against non-State actors are also discussed in the article. It is argued that the “gravity” criterion used by the ICJ seems controversial and, consequently, may limit the right of self-defence. On the other hand, however, the judgment established a strong barrier to the realization of individual political interests by militarily powerful States. This is the Nicaragua judgment’s long-lasting legacy.In this sense the judgment has stood the test of time.